FAKTOR – FAKTOR YANG MEMPENGARUHI PEMANFAATAN POSBINDU PTM (PENYAKIT TIDAK MENULAR) DI MASYARAKAT WILAYAH KERJA PUSKESMAS PAAL X KOTA JAMBI TAHUN 2024 - Matda Yunartha (Nightingale: Journal of Nursing, 2024)
One form of community participation in carrying out early detection and monitoring ofNCD risk factors is through Posbindu PTM. Posbindu is a form of UKBM under theguidance of the Community Health Center in controlling NCD risk factors which iscarried out in an integrated, routine and periodic manner. The aim of the research is tofind out what factors influence the use of Posbindu PTM in the community in the PaalThe sample was 106 respondents. Data was collected using a questionnaire. How toanalyze univariate and bivariate. The test used in this research is Chi-Square. Theresults of this research showed that there was a relationship between knowledge (0.000),attitude (0.0031), support from health workers (0.000) and family support (0.000) withthe use of Posbindu PTM. The Posbindu PTM activity is a very effective activity inmonitoring health status to control the incidence of Non-Communicable Diseases, sothere needs to be increased knowledge and support from various parties, including theHealth Service, Community Health Center, family support and the community itself.